INTERNALISASI BIAYA LINGKUNGAN PADA BUDIDAYA IKAN KARAMBA JARING APUNG DI WADUK CIRATA - Urip Rahmani; Yusman Syaukat; Akhmad Fauzi; Aceng Hidayat (Indonesian Journal of Agricultural Economics, 2011)
Activity floating net cage (Karamba Jaring Apung-KJA) in Reservoir Cirata have beenover capacity, so that give the serious problems such as water quality degradation,algae-blooming, and up-welling. The objective of this research is to find the optimuminput cage net without and with cost externality. The objective, was solved by costfunction of KJA (cage net) culture activity with/without externality model. Theexternality of cage net culture to water body of Waduk Cirata has been gived a sedimentaccumulation until 325711 ton/year and make degradate of water quality. For cage netculture, water quality is environment input. Model research involved this externality inmodel of cost function. It is by internalize cost environmet as the one’s of costproduction. Input of production factor of KJA culture activity without externality werecost of seed, feed and labour, and with externality was added by cost of recoverysediment by dredging or exploition. Optimal input of seed 46,28 kg/plot, feed 1685,02kg/plot, 122,09 work person daya (wpd)/unit, activity without externality and optimalharvest product 938,16 kg. While for KJA activity with cost environment, seed wassignificant change, 31,66 kg and feed 756,24 kg, 50,92 work person day person/unit,and amount of sediment 15,25 kg/unit with optimal harvest 644,6 kg/plot. Using of theCirata Data Environment and CAD_S tool software, the carrying capacity of ReservoirCirata for KJA culture activity have found was 43.679 ton/year. For activity withoutexternality, amounts optimal of KJA 15585 plots, and seed using 1464,7 kg/plot. Forwith-externality activity 21133 plots KJA, and seed using 756,24 kg/plot. It is mean adecreasing feed costs 44,88%.Keywords: externality, cost, cost function, optimal input, optimal product, carryingcapacity